Trait–environment diagnosis of ecological instability in Korean streams using benthic diatoms and machine learning: a UMAP–CDI framework - Jun-Ho Lee; Hyo Gyeom Kim; Byeong-Hun Han; In-Hwan Cho; Ha-Kyung Kim; Eun-A. Hwang; Su-Ok Hwang; Baik-Ho Kim (Aquatic Sciences, 2026)

Applicability of plant–clay mineral composite for rapid algae removal from eutrophic freshwaters at the laboratory and field scales - Byeong-Hun Han; Hyo Gyeom Kim; Young-Hyo Kim; In-Hwan Cho; Ha-Kyung Kim; Sungwon Hong; Baik-Ho Kim (Environmental Research, 2025)

Impact of administration routes and dose frequency on the toxicology of SARS-CoV-2 mRNA vaccines in mice model - Jae-Hun Ahn; Jisun Lee; Gahyun Roh; Na-Young Lee; Hee-Jin Bae; Euna Kwon; Kang-Min Han; Ji-Eun Kim; Hyo-Jung Park; Soyeon Yoo; Sung Pil Kwon; Eun-Kyoung Bang; et al. (Archives of Toxicology, 2025)
The increasing use of SARS-CoV-2 mRNA vaccines has raised concerns about their potential toxicological effects, necessitating further investigation to ensure their safety. To address this issue, we aimed to evaluate the toxicological effects of SARS-CoV-2 mRNA vaccine candidates formulated with four different types of lipid nanoparticles in ICR mice, focusing on repeated doses and administration routes. We conducted an extensive analysis in which mice received the mRNA vaccine candidates intramuscularly (50 μg/head) twice at 2-week intervals, followed by necropsy at 2 and 14 dpsi (days post-secondary injection). In addition, we performed a repeated dose toxicity test involving three, four, or five doses and compared the toxicological outcomes between intravenous and intramuscular routes. Our findings revealed that all vaccine candidates significantly induced SARS-CoV-2 spike protein-specific IgG and T cell responses. However, at 2 dpsi, there was a notable temporary decrease in lymphocyte and reticulocyte counts, anemia-related parameters, and significant increases in cardiac damage markers, troponin-I and NT-proBNP. Histopathological analysis revealed severe inflammation and necrosis at the injection site, decreased erythroid cells in bone marrow, cortical atrophy of the thymus, and increased spleen cellularity. While most toxicological changes observed at 2 dpsi had resolved by 14 dpsi, spleen enlargement and injection site damage persisted. Furthermore, repeated doses led to the accumulation of toxicity, and different administration routes resulted in distinct toxicological phenotypes. These findings highlight the potential toxicological risks associated with mRNA vaccines, emphasizing the necessity to carefully consider administration routes and dosage regimens in vaccine safety evaluations, particularly given the presence of bone marrow and immune organ toxicity, which, though eventually reversible, remains a serious concern.

Daily and seasonal changes of sap flow in Gamhong apple cultivar and estimate the tree-level transpiration using Penman-Monteith reference evapotranspiration - Narayan Bhusal; Louis S. Santiago; Joncheon Lee; Sanghak Jeong; In Hee Park; Byeong-Ho Choi; Hun-Joong Kweon; Su-Gon Han; Tae-Myung Yoon (South African Journal of Botany, 2024)